Student Self-Regulation during Online Lecture During the Covid-19 Pandemic at Muhammadiyah University of Sidoarjo - Rahmawati Wahyu Onggo Wicono; Ghozali Rusyid Affandi (Universitas Muhammadiyah Sidoarjo, 2022)
Self-regulation is an impulse from within (internal), which can lead to an individual's desire to determine or identify goals in life, plan strategies that will be carried out in achieving these goals, and evaluate and modify behavior. that will do. The purpose of this study was to find out how the description of self-regulation in students during online lectures at the Muhammadiyah University of Sidoarjo. The population selected in this study were all students from 5 faculties at the Muhammadiyah University of Sidoarjo, totaling 11.914 students with the characteristics of active students, semester I – VIII, and taking online lectures. The total population in this study was 11.914, so that when viewed from the table Krejcie and Morgan, a sample of 375 people was obtained. This study uses a data collection technique in the form of a psychological scale, namely a self-regulation scale developed by the researcher through aspects of self-regulation according to Zimmerman (Ghofar, 2014) with a total of 54 statements in the form of a Likert scale. From the results of the validity test, 46 items were valid from 54 items. The result of the reliability test is 0.939. The results showed that students' self-regulation during online lectures at Muhammadiyah University of Sidoarjo was generally in the moderate category. And the aspect of self-regulation that is most widely applied by students of Muhammadiyah University of Sidoarjo is the aspect of motivation.